BRITISH SILURIAN STROMATOPOROIDS. FAUNAS, PALAEOBIOLOGY, AND PALAEOGEOGRAPHICAL SIGNIFICANCE. Issue 660 (4th May 2021) - Kershaw, Stephen; Christine, Anne-; Silva, Da; Sendino, Consuelo
ABSTRACT: Recommended reference to this publication: Kershaw, S., Da Silva, A.-C. & Sendino, C. 2021. British Silurian stromatoporoids. Fauna, palaeobiology, and palaeogeographical significance. Monograph of the Palaeontographical Society, London: 1-92; pls 1-22. (Publ. No. 660, part of Vol. 175 for 2021.) British Silurian stromatoporoids occur in carbonate rocks, mostly in the Wenlock Series, together with a small number in the Llandovery Series and very few in the Ludlow Series. Using field and museum material (408 samples) and literature, this study identifies 15 stromatoporoid genera, doubling the previously known generic diversity, so the British Isles holds the third highest genera-diversity Wenlock assemblage after Gotland/Estonia (23 genera) and the Siberian Platform (20 genera). Remarkably, nearly all samples come from the small (100 × 100 km) Much Wenlock Limestone Formation (MWLF) (Homerian Stage, uppermost Wenlock Series) in the Midland Platform of central England (Avalonia), surrounded, underlain, and overlain by siliciclastics. On the Midland Platform one sample is Llandovery age; 11 samples are Ludlow age (Aymestry Limestone). Other samples from the Isle of Man (Wenlock age, six samples) and south-west Scotland (Llandovery age, three samples) are in transported material, with associated corals and they indicate unpreserved carbonate platforms in northern Britain. A few Llandovery Series stromatoporoids are also reported from Ireland, both north and south of the Iapetus Suture; published reports of Wenlock stromatoporoids from Ireland are shown to be misidentified trace fossils. In the MWLF stromatoporoids (together with the more abundant rugose corals, tabulates, heliolitids, and some microbial carbonates) occur in small patch reefs and in bedded bioclastic grainstones, packstones, and nodular wackestones; stromatoporoids are more common in and near patch reefs. The MWLF stromatoporoid fauna has 15 confirmed low-level taxa: Labechia conferta (Lc), Lophiostroma schmidti (Ls), Ecclimadictyon macrotuberculatum (Em) and E. astrolaxum (Ea), Petridiostroma simplex (Ps) and P. linnarssoni (Pl), Actinostromella vaiverensis (Av), Araneosustroma fistulosum (Af), Densastroma pexisum (Dp), Plectostroma intertextum (Pi), Simplexodictyon yavorskyi (Sy), Eostromatopora impexa (Ei), 'Stromatopora' venukovi ('S'v), Syringostromella borealis (Sb) and Parallelostroma typicum (Pt) . No new taxa were found. The five most abundant taxa (Lc, Av, Dp, Px, and Sb ) total 230 specimens, 64.2% of the MWLF assemblage, consistent with taxa proportions in other Palaeozoic stromatoporoid assemblages. The stromatoporoids have limited growth forms: Lc grew laminar frames, mostly in patch reefs; the other taxa range from laminar to high domical, maximum sizes around 40 cm basal diameter. They almost completely lack the complexities and diversities of form of their contemporaries in nearby large carbonate platforms of Baltica (Gotland/Estonia) and Laurentia (eastern USA and Canada); only two samples contain intergrown corals. Overall, British Silurian stromatoporoids may be viewed as a relatively limited shallow marine assemblage that took advantage of suitable conditions in a short time-and-space window in an episode of raised sea level with low siliciclastic input. The MWLF has the largest assemblage in the Avalonia microcontinent at the end of the Wenlock Epoch. Palaeogeographically, the Avalonia assemblage of stromatoporoids lay in an important location between Laurentia, Baltica and other Silurian continents and may have aided distribution pathways of stromatoporoids that presumably had planktonic forms for migration. Stromatoporoids were likely not affected by the mid-Silurian extinction event, but data are insufficient to be certain. Les stromatoporoïdes de Silurien de Grande-Bretagne. Faunes, paléobiologie et signification paléogéographique